Discrepancies between the modeled and proxy‐reconstructed response to volcanic forcing over the past millennium: Implications and possible mechanisms. Issue 14 (24th July 2013) - Mann, Michael E.; Rutherford, Scott; Schurer, Andrew; Tett, Simon F.B.; Fuentes, Jose D.
Abstract : [1] We show that a systematic discrepancy between model simulations and proxy reconstructions of hemispheric temperature changes over the past millennium appears to arise from a small number of radiatively large volcanic eruptions. Past work has shown that accounting for this mismatch alone appears to reconcile inconsistencies between the overall amplitude of simulated and proxy‐reconstructed temperature changes. We provide empirical support for the previously posited hypothesis that this discrepancy may arise from threshold growth effects in tree line‐proximal trees that limit their response to large volcanic cooling events. Such threshold responses could lead to an absence of growth rings (as many as six accumulated years over the past eight centuries) for some fraction of tree line‐proximal trees, leading to a potential misalignment of volcanic cooling events in trees from climatically distinct regions, and a further attenuation and smearing of the volcanic cooling signal. Since the high‐frequency component of nearly all proxy reconstructions of past hemispheric temperature change is derived from tree ring data, this bias would likely impact nearly all such reconstructions. We show here that the discrepancy may have led to an underestimation bias in past studies attempting to infer equilibrium climate sensitivity from proxy temperature reconstructions of the past millennium. Key Points: mismatch between modeled and proxy‐reconstructed volcanic cooling models and reconstructions can be reconciled if threshold effects accounted for empirical evidence supports biases in tree‐ring volcanic cooling estimates